The effects of some exergetic indicators on the performance of thin layer drying process of long green pepper in a solar dryer - Akpinar, Ebru Kavak (Springer, 2019)
In this study, exergy analysis of the thin layer drying process of long green pepper was performed in solar dryer with forced convection. The effects of some exergetic indicators on the performance of a thin layer solar drying system by using the experimental data in the literature for long green pepper (Akpinar and Bicer in Energy Convers Manag 49: 1367-1375, 2008) were investigated. For this purpose, the exergetic indicators such as exergetic efficiency, waste exergy ratio, environmental impact factor, exergetic sustainability index and improvement potential, previously used in the literature, were taken into account (Zisopoulos et al. in Crit Rev Food Sci Nutr 57(1):197-211, 2017, Midilli and Kucuk in Int J Exergy 16(3): 278-292, 2015, Van Gool 1997). The exergetic efficiency and improvement potential of the solar drying system decreased with the increase of drying time. The waste exergy ratio increased with the increase of drying time. The exergetic sustainability index increased with increasing the exergetic efficiency, decreased with decreasing the exergetic efficiency. The environmental impact factor decreased with increasing the exergetic efficiency.
Keywords: Solar drying; Forced drying; Long green pepper; Exergetic indicators